2008
DOI: 10.1111/j.1365-2559.2008.03083.x
|View full text |Cite
|
Sign up to set email alerts
|

Morules in endometrioid proliferations of the uterus and ovary consistently express the intestinal transcription factor CDX2

Abstract: Typical squamous elements and morules have an overlapping but differing immunophenotype. Morules exhibit no firm immunohistochemical or ultrastructural evidence of squamous differentiation, although immature squamous differentiation cannot be excluded. Nuclear beta-catenin positivity is in keeping with the observation that endometrioid glandular lesions with morules are often associated with beta-catenin gene mutation. The explanation for diffuse nuclear positivity with the intestinal transcription factor CDX2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
61
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 39 publications
7
61
0
Order By: Relevance
“…[30][31][32][33][34][35] In general, more than 90% of colorectal ADCs and small bowel ADCs are positive for CDX2. However, marked reduction or loss of expression of CK20 and CDX2 was frequently seen in medullary carcinoma of the large intestine.…”
Section: Review Of Selected Antibodiesmentioning
confidence: 99%
“…[30][31][32][33][34][35] In general, more than 90% of colorectal ADCs and small bowel ADCs are positive for CDX2. However, marked reduction or loss of expression of CK20 and CDX2 was frequently seen in medullary carcinoma of the large intestine.…”
Section: Review Of Selected Antibodiesmentioning
confidence: 99%
“…95,96 Furthermore, a curious pattern of CDX2 expression has been documented in the ''squamous'' morules of endometrioid hyperplasia and carcinoma. 97,98 Adenocarcinomas arising within germ cell tumors often show intestinal differentiation, as evidenced by CDX2 expression. 83,84 Villin.-Villin is an actin-binding protein, found preferentially in microvilli, expression of which is largely (but not entirely) restricted to glandular epithelium and corresponding adenocarcinomas of the GI tract.…”
mentioning
confidence: 99%
“…It has been well established that caudal type homeobox 2 (CDX2) is a highly sensitive immunomarker for gastrointestinal (GI) adenocarcinomas but may also be expressed in tumors from other organs, such as the pancreas, bile ducts, bladder, uterine cervix, endometrium, and ovary. [10][11][12][13][14][15] Marked reduction or loss of expression of cytokeratin 20 (CK20) and CDX2 is frequently seen in MC. 9,[16][17][18][19] Wick and colleagues 20 reported that multifocal positivity of neuroendocrine markers (synaptophysin and chromogranin A) and focal p53 positivity were observed in 32% and 53% of MC cases, respectively.…”
mentioning
confidence: 99%